Immunogold Electron-Microscopic Localization of Calpain I in Human Erythrocytes - Samis, John A; Elce, John S (Thrombosis and Haemostasis, 1989)
With a view to understanding the function of calpain I (EC 3.4.22.17) in vivo, the localization of the enzyme was studied by immunoelectron microscopy in human erythrocytes. Thin sections of the cells embedded in Spurr’s resin were exposed to solutions of monoclonal anti-calpain I or control antibodies, biotin antimouse IgG antibodies, and streptavidin-gold. Most of the calpain I (93%) was found to be distributed throughout the cytoplasm, and only 7% of the gold particles were associated with the erythrocyte membrane. Erythrocytes were Ca2+-loaded by means of the calcium ionophore A23187, and the rise in intracellular [Ca2+] was demonstrated both by crenation of the cells, and by activation of calpain which was detected by immunoblotting. The proportions of cytosolic and membrane-bound gold labelling were, however not altered by Ca2+-loading. These results are not consistent with the hypothesis that activation of calpain requires membrane-binding.
Keywords: Calpain; Erythrocytes; Immunohistochemistry; Ca2+; loading